Why the mass and proper time must be considered as dynamical variables. (11th June 2019) - Greenberger, Daniel M
Abstract: We present a 'proof' that the standard treatment of the mass and proper time as parameters, rather than dynamical variables, is actually inconsistent, and we show how they can be introduced as a generalization of the standard Hamiltonian Dynamics. We discuss various topics such as the equivalence principle and particle decay and the uncertainty principle from this point of view. I am honored to be able to give this talk as part of the 60th birthday festival for professor. Wolfgang Schleich, a long-term colleague, a very good friend, and a beloved and highly respected member of the quantum community, and I hope our collaboration can continue for many years to come. I extend my best wishes to him and his wonderful wife Kathy on this occasion.